Disenchanting Les Bons Temps : Identity and Authenticity in Cajun Music and Dance - Stivale, Charles J. (Book collections on Project MUSE., 2003)
Presents the complex and conflicting views of Cajun cultural heritage, identities, and their manifestation in musical and dance expression.